How smart policies can lessen effects of climate change - Richard Munang; Robert Mgendi (Africa Renewal, 2016)
According to a famous African proverb, “When the music changes, so does the dance.” This adage illustrates the continent’s current position amidst opportunities for, and challenges to, development and governance as the 21st century unfolds.